Biological and Physical Characterization of Surface-Modified Grade V Titanium Alloy - Mahesh Kakunje; Supriya Nambiar; Arun M. Isloor; Shamaprasada Kabekkodu; Udaya Bhat (Hindawi Limited, 2024)
Surface modification and biomimetic approaches have been widely used to enhance bioinert substances. It is not very clear whether surface alterations and polymer coatings on titanium make it more biologically active and enhance cell adhesion. We tried to focus on the physical and biological characterization of surface-modified titanium disks. Four different surface modifications were done for the titanium disks, ranging from acid etching, sandblasting, polydopamine coating, and polydopamine-based chitosan coating, and were compared with disks without any surface modification. The disks were studied for physical characteristics like surface roughness and contact angle. Human gingival fibroblasts were used to investigate the biological effects of surface modification of titanium alloy surfaces. The wettability of chitosan-coated, acid-etched, and polydopamine-coated titanium was much better than that of the sandblasted surface, indicating that surface energy was higher for acid-etched and coated surfaces than others. The cell seeding with fibroblasts showed increased adhesion to the smoother surfaces as compared to the rougher surfaces. Polydopamine coatings on titanium disks showed the most favorable physical and biological properties compared to others and can be a good surface coating for in vivo implants.